The safety of neoadjuvant chemotherapy combined with non-tube nofasting fast-track surgery for esophageal carcinoma - Zheng, Yan; Hao, Wentao; Li, Yin; Liu, Xianben; Wang, Zongfei; Sun, Haibo; Liu, Shilei; Xing, Wenqun (Frontiers in Oncology, 2022)
Objectives: To evaluate the impact of early oral feeding (EOF) combined with neoadjuvant chemotherapy (NAC) on the safety of McKeown minimally invasive esophagectomy (MIE). Summary Background Data: Our non-tube no fasting (early oral feeding and no nasogastric tube) fast-track surgery (FTS) was safe and effective for primary surgery esophageal cancer patients. Methods: We retrospectively evaluated consecutive patients who underwent non-tube no fasting and MIE. They were divided into two groups: one received NAC, and the other received primary surgery. Complications after the operation, postoperative CRG complications, operative time, operative bleeding, and length of stay were evaluated. Results: Between 01/2014 and 12/2017, 382 consecutive patients underwent minimally invasive esophagectomy with total two-field lymphadenectomy under the nontube nonfasting fast-track surgery program. A total of 137 patients received NAC, and 245 accepted primary surgery. Propensity score matching was used to compare NAC patients with 62 matched patients from each group. The NAC group had a similar number of total complications as the primary surgery group (32.26% in the primary surgery group vs. 25.81% in the NAC group; p=0.429) and had the same median postoperative hospitalization duration (8 days, p=0.723). Conclusions: After McKeown minimally invasive esophagectomy, the patients receiving NAC combined with “non-tube no fasting” FTS had a similar incidence of postoperative complications outcomes as those without NAC. In addition, the two groups were similar in terms of the recovery time, hospital discharge day, and early resumption of oral feeding.